2011
DOI: 10.2139/ssrn.1957156
|View full text |Cite
|
Sign up to set email alerts
|

The Happy Artist? An Empirical Application of the Work-Preference Model

Abstract: The artistic labor market is marked by several adversities, such as low wages, above-average unemployment, and constrained underemployment. Nevertheless, it attracts many young people. The number of students exceeds the available jobs by far. A potential explanation for this puzzle is that artistic work might result in exceptionally high job satisfaction, a conjecture that has been mentioned at various times in the literature. We conduct the first direct empirical investigation of artists' job satisfaction. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…It is quite common and effective to study the motivation and self‐efficacy of entrepreneurs by means of self‐completed questionnaires (e.g. Simoens & Tervaniemi, ) and current research on the psychology of artists and other creative professionals shows that surveys constitute a “satisfactory empirical approximation of individual utility” (Steiner & Schneider, , p. 230). We developed our online questionnaire based on validated scales in the SDT and entrepreneurship literature that were translated from English to Dutch, backward and forward independently by two of the authors.…”
Section: Methodsmentioning
confidence: 99%
“…It is quite common and effective to study the motivation and self‐efficacy of entrepreneurs by means of self‐completed questionnaires (e.g. Simoens & Tervaniemi, ) and current research on the psychology of artists and other creative professionals shows that surveys constitute a “satisfactory empirical approximation of individual utility” (Steiner & Schneider, , p. 230). We developed our online questionnaire based on validated scales in the SDT and entrepreneurship literature that were translated from English to Dutch, backward and forward independently by two of the authors.…”
Section: Methodsmentioning
confidence: 99%
“…The hypothesis that artists are primarily concerned with artistic valuation and appreciation, has been directly tested by looking at artists’ job satisfaction compared with that of other groups. Studies by Bille et al () and Steiner and Schneider () confirmed that, on average, artists are considerably more satisfied with their work than non‐artists, a finding that supports the work‐preference model. Differences in income, working hours, and personality cannot account for the observed difference in job satisfaction.…”
Section: Artists’ Labor Marketmentioning
confidence: 76%
“…In this case, arts work is included as an argument in the utility function, and the model is often called the work‐preference model (Throsby, , ). Studies have found that non‐pecuniary benefits are among the key reasons for preferring to be an artist (Steiner and Schneider, ; Bille, Frey, Steiner and Fjællegaard, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, qualification requirements are very demanding as musical actors have to learn singing, dancing and acting up to a professional level. Moreover, the prospects of being part of a musical show attract so many actors that the labor market is largely over-supplied, while demand is stagnant or even shrinking (compare also e.g., [36]). On the other hand, however, it is often necessary to get out, even after a foothold in the business has been gained.…”
Section: Methodsmentioning
confidence: 99%